2008
DOI: 10.1007/s12247-008-9039-x
|View full text |Cite
|
Sign up to set email alerts
|

Needle-Free Delivery of Powdered Protein Vaccines: A New and Rapidly Developing Technique

Abstract: Skin is an attractive tissue for vaccine delivery.Recently, interest has focused on dry powder injectors for needle-free vaccination. This review summarizes the current knowledge on this innovative application technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Classical freeze-drying does not lead to distinct particles, but rather to the wellknown cake structure that has to be disaggregated in a subsequent step, usually leading to a very wide particle size distribution with a substantial fine powder fraction that cannot be used for needle-free delivery. A summary of other methods for the manufacture of powders for needle-free injection can be found in the literature (Burkoth et al 1999;Ziegler 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Classical freeze-drying does not lead to distinct particles, but rather to the wellknown cake structure that has to be disaggregated in a subsequent step, usually leading to a very wide particle size distribution with a substantial fine powder fraction that cannot be used for needle-free delivery. A summary of other methods for the manufacture of powders for needle-free injection can be found in the literature (Burkoth et al 1999;Ziegler 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ziegler (2008) has shown that acceptable DNA vaccination requires the coated micro-particle to penetrate the skin surface with around 20-100 mm penetration depth. It indicated that needle-free biolistic micro-particle injection achieves a more efficient pharmaceutical effect than diffusion delivery.…”
Section: Effects Of Physical Approaches To Drug Deliverymentioning
confidence: 99%
“…The micro‐particles are generally required to penetrate to certain depths within the target to carry out the desired effect of gene delivery and, as such, the penetration depth of the micro‐particles is one of the major variables studied in gene delivery research. Ziegler has indicated that an acceptable DNA delivery requires that the micro‐particles penetrate into the target skin tissue by approximately 20 ± 100 μm. However, the top layer of the skin, that is the stratum corneum , limits the penetration depths for the particles because of its resistance to particle motion.…”
Section: Introductionmentioning
confidence: 99%